Analisis Metode Springate Dalam Memprediksi Kebangkrutan Pada Perusahaan Asuransi Yang Terdaftar di BEI - Purwantoro, Aletha Kevina Putri; Nadia, Ananta Arta; Anggraeni, Dwi; Alamsyah, Naditha Ersa Auryn; Ramadhan, Yanuar (Universitas Sains dan Teknologi Komputer, 2025)
Unstable financial conditions in insurance companies can serve as an early indicator of potential bankruptcy, which may have wide-ranging impacts on policyholders, shareholders, and the overall stability of the financial sector. Therefore, early detection of bankruptcy risk is critically important. This study aims to evaluate the effectiveness of the Springate model in identifying potential bankruptcy among insurance companies listed on the Indonesia Stock Exchange during the 2022–2024 period. The Springate model was chosen due to its simplicity and its ability to provide quantitative insights into a company's financial condition. Data were collected from the annual financial statements of 16 companies selected through purposive sampling based on the completeness and consistency of their financial reporting. The model applies the S-Score calculation as the basis for classifying companies into financial distress or non-financial distress categories. The analysis revealed that six companies consistently exhibited signs of financial difficulty, with three of them identified as being in a state of financial distress for three consecutive years. Meanwhile, the other ten companies demonstrated stable and healthy financial conditions throughout the observation period. These findings indicate that the Springate model is reasonably practical as an early detection tool for bankruptcy risk, particularly in the insurance sector, which is influenced by various internal factors such as risk management, as well as external factors like economic fluctuations and government regulations. Therefore, this model can be utilized as a decision-support tool for both management and investors in making strategic financial decisions.